Effects of total abdominal irradiation on gut microbiota and metabolome during acute tissue injury - Lu, Lina; Huang, Qingyu; Sun, Chao; Kang, Shuhe; Jin, Pen; Wang, Xin; Luo, Xingping; Li, Jia (Frontiers in Microbiology, 2025)
ObjectiveRadiation-induced intestinal injury is the most common complication following radiotherapy for pelvic tumors. Effective clinical treatments remain limited, and its underlying mechanism remains unclear. Using a mouse model, this study dynamically characterizes the progression of acute radiation-induced intestinal injury through integrated analysis of the gut microbiota and metabolome, thereby supporting the development of rational therapeutic strategies.MethodsMice received a single 12 Gy dose of total abdominal irradiation. Feces were collected for microbiota and metabolomic analysis, and intestinal tissues were harvested at 24 h and 3 days post-irradiation. These tissues underwent both histopathological assessment and analysis of inflammatory signaling pathways.ResultsTotal abdominal irradiation induced severe intestinal injury. At 24 h post-irradiation, intestinal mucosal cell nuclei were fragmented and intestinal permeability increased. The damage progressively worsened, and by 3 days, villi had shortened, nuclear fragmentation was more extensive, and eosinophilic granulocytes had infiltrated the tissue. Bioinformatic analysis of microbiota data revealed gut dysbiosis during the acute injury phase, characterized by reduced α-diversity, an elevated abundance of g_Escherichia-Shigella, f_Enterobacteriaceae, and decreased levels of f_Ruminococcaceae, g_Lachnospiraceae_NK4A136, and other butyrate-producing bacteria. This dysbiosis led to elevated fecal lipopolysaccharide levels and activation of the TLR4/MyD88/NF-κB inflammatory signaling cascade. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis indicated that abdominal irradiation predominantly affected lysine degradation, arginine and proline metabolism, primary bile acid synthesis, tryptophan metabolism, taurine metabolism, and sphingolipid metabolism. The effects on lysine degradation, sphingolipid metabolism, and primary bile acid biosynthesis were especially pronounced.ConclusionOverall, these data indicate that radiation exposure disrupts both the gut microbiota and metabolome during the acute injury phase, reducing beneficial bacteria such as f_Ruminococcaceae and Bifidobacterium while promoting the proliferation of harmful bacteria such as g_Escherichia-Shigella, which in turn triggers an inflammatory metabolic cascade. Early restoration of a normal gut microbiota could be one of the potential steps to mitigate the radiation effect based on prior literature. These findings provide a scientific basis for future research into microbiota- and metabolome-targeted therapies aimed at mitigating radiation-induced intestinal toxicity.